Mengelola Penyusunan Modul Pembelajaran Dasar Perbankan Bagi Siswa Sekolah Menengah Kejuruan Provinsi Banten - Taufik Raharjo; Ambang Aries Yudanto; Pratin Pratin (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this community service activity is to compile a textbook for basic banking learning modules. The method of implementing this service activity is divided into three stages, namely planning, implementation, and evaluation. At the planning stage, a work plan, division of tasks, and implementation schedule are formulated. For the implementation phase, the team was divided into six consisting of four MGMP teams and two teams of devotees (PKN STAN) and the final result was a concept of a basic banking learning module book with a plagiarism check result at 27%. In the last stage, the service and partners concluded that this community service activity was declared successful, namely by completing the concept of the banking learning module book for vocational students in Banten Province. However, this book that has been compiled has not yet been published by a book publisher. This is due to a change in the semester program.